Serial EXTEM, FIBTEM, and tPA Rotational Thromboelastometry Observations in the Maastricht Intensive Care COVID Cohort—Persistence of Hypercoagulability and Hypofibrinolysis Despite Anticoagulation - Hulshof, Anne-Marije; Brüggemann, Renée A. G.; Mulder, Mark M. G.; van de Berg, Tom W.; Sels, Jan-Willem E. M.; Olie, Renske H.; Spaetgens, Bart; Streng, Alexander S.; Verhezen, Paul; van der Horst, Iwan C. C.; Ten Cate, Hugo; Spronk, Henri M. H.; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: Coronavirus Disease 2019 (COVID-19) patients often present with thromboembolic events. In COVID-19 patients, routine hemostatic assays cannot correctly identify patients at risk for thromboembolic events. Viscoelastic testing with rotational thromboelastometry (ROTEM) might improve the characterization of COVID-19-associated coagulopathy. Objective: To unravel underlying coagulopathy and fibrinolysis over time as measured by serial assessment heparin-independent (FIBTEM and EXTEM) and fibrinolysis illustrating (tissue plasminogen activator; tPA) ROTEM assays. Patients/Methods: Between April 23 and June 12, consecutive adult patients enrolled within the Maastricht Intensive Care COVID (MaastrICCht) cohort were included, and a comprehensive set of clinical, physiological, pharmaceutical, and laboratory variables were collected daily. Twice per week, EXTEM, FIBTEM, and tPA ROTEM were performed. Clotting time (CT), clot formation time (CFT), maximum clot firmness (MCF), lysis onset time (LOT), and lysis time (LT) were determined to assess clot development and breakdown and were compared to routine hemostatic assays. Results: In 36 patients, 96 EXTEM/FIBTEM and 87 tPA ROTEM tests were performed during a 6-week follow-up. CT prolongation was present in 54% of EXTEM measurements, which were not matched by prothrombin time (PT) in 37%. Respectively, 81 and 99% of all EXTEM and FIBTEM MCF values were above the reference range, and median MCF remained elevated during follow-up. The ROTEM fibrinolysis parameters remained prolonged with median LOT consequently >49 min and unmeasurable LT in 56% of measurements, suggesting a severe hypofibrinolytic phenotype. Conclusion: ROTEM tests in COVID-19 ICU patients show hypercoagulability and severe hypofibrinolysis persisting over at least 6 weeks.